Epidemic spreading with an awareness-based adaptive mechanism in temporal multiplex networks - Xiong, Wenze; Zhou, Chunjie (Frontiers in Physics, 2023)
Social interaction which is intricate and time-varying has emerged as a pivotal consideration in the epidemic spreading. In this paper, we devise a UAU-SIS model for simulating the awareness diffusion and epidemic spreading on temporal multiplex networks. Drawing inspiration from individuals' self-protection behaviors, a novel adaptive update mechanism is developed.To provide a more precise representation of the collective social interactions encompassing individuals, we introduce the higher-order network structure encompassing temporal variability.Building upon the established framework of the MMCA method for static networks, we extend its applicability to the condition of temporal networks and derive the threshold within the coupled dynamics. Our extensive simulations illuminate the dual role of awareness in epidemic mitigation.Beyond solely diminishing infection probabilities through self-protective measures, individual awareness additionally facilitates to change the network structure to seperate them from the infected. By elucidating these fundamental characteristics, our research contributes to advancing more effective strategies for epidemic mitigation and containment.